Effectiveness of microfinance institutions in empowering of women petty traders’ performance: The case of Pride Tanzania Ltd – Morogoro branch - Ngitoria, Damnoti (Mzumbe University, 2024)
A research report submitted to Mzumbe University as a partial fulfillment of the requirement for the award of the degree of Master’s of Business Administration (MBA) of Mzumbe University